Scene setting activities: One of studentsâ learning motivation factor - Ansar, Ansar; Afiif, Ahmad; Damayanti, Eka (Jurnal Pendidikan Biologi Indonesia, 2018)
Apperception at the beginning of teaching and learning process is the common activity done by the teacher which determine the effectiveness of the process. This study aimed to determine the relationship between scene setting at the beginning of the learning process and studentâs learning motivation. This was a correlational research in which the population was seventh-grade students at MTs. Madani Alauddin Pao Pao. The number of samples was sixty students, taken from 50% of the population by using simple random sampling. The instruments used were scene setting activity observation sheet and motivational questionnaire sheet, they both used the Likert scale. The data obtained were analyzed using simple linear regression analysis. The results indicated that there was a significant correlation between the scene setting and students learning motivation in Integrated Science subject in class VII of MTs. Madani Alauddin Pao Pao (p < 0.05). The relation between scene setting and learning motivation was in a strong category (R = 0.600). Thus, the better the scene setting activities, the more optimum the studentsâ motivation.Â